Reorganization of the Library Fund of the Republic in Uzbekistan - Rakhmatullaeva Saodat Ibragimovna (Genius Journals, 2022)
The article analyzes the issues of reorganization of the fund of the republic's libraries and enrichment of the library fund with national publications during the years of independence. Also, issues such as how the library staff helped to promote humanitarianism and widely spread the decisions and decrees issued by the government of the republic among the population were highlighted
Keywords: library; decision; decree